Detection of microplastics using inductively coupled plasma-mass spectrometry (ICP-MS) operated in single-event mode. Issue 3 (16th December 2019) - Bolea-Fernandez, Eduardo; Rua-Ibarz, Ana; Velimirovic, Milica; Tirez, Kristof; Vanhaecke, Frank
Abstract : The occurrence of microplastics (MPs) in the environment is a matter of increasing concern. In this work, it has been shown for the first time that ICP-MS operated in single-event mode can be used for the characterization of MPs relying on their C content. Abstract : The occurrence of microplastics in many, if not all environmental compartments is a matter of increasing concern and deserves proper attention. However, there is still a lack of analytical tools for straightforward monitoring of these tiny plastic particles at environmentally relevant levels in water. Inductively coupled plasma-mass spectrometry (ICP-MS) operated in single-particle mode (SP-ICP-MS) was demonstrated to be a powerful technique for the characterization of metallic nanoparticles, but to the best of the authors' knowledge, SP-ICP-MS has not yet been evaluated for the purpose of detection of microplastics and their quantitative determination (particle number density). In this work, spherical polystyrene microspheres of 1 and 2.5 μm – to mimic microplastics coming from plastic waste – have been detected using ICP-MS. The approach developed relies on the ultra-fast monitoring of transient signals (with a dwell time of 100 μs) when using a quadrupole-based ICP-MS unit in the so-called single-event mode and registering the signal spikes produced by individual microparticles by monitoring the signal intensity at a mass-to-charge ratio ( m / z ) of 13 ( 13 C + ). The accuracy of the number-based concentration results (particle number densities) has been assessed by comparing the number of events detected when monitoring 13 C + to those detected when monitoring 165 Ho + for 2.5 μm lanthanide-doped polystyrene beads. Additionally, the results obtained for both polystyrene microspheres in terms of size (most frequently occurring intensity of the signal distribution) compare well with the size as determined using electron microscopy. ICP-MS operated in single-event mode thus allows information on both the size distribution and mass concentration of microplastics to be obtained. As this approach makes use of instrumentation already available in many routine labs analyzing environmental samples, it can enable these labs to analyze microplastics by using their instrument in single-event mode.